Sonication results in variable quality and enhanced sensory attributes of Adajamir (Citrus assamensis) juice: A study on an underutilized fruit - Hasan Ahmad; Tariqul Islam; Zohurul Islam; Fahad Jubayer; Rahmatuzzaman Rana (Heliyon, 2023)
Citrus assamensis, commonly known as Adajamir, is an underutilized fruit with distinctive sensory and nutritional properties. The limited amount of research on this particular citrus type was recognized as one of the research gaps for this study. The objective of this study was to evaluate and compare the impacts of sonication, pasteurization, and thermosonication techniques on the quality and sensory attributes of Adajamir juice. A randomized experimental design was used in the study, wherein the juice underwent three different treatments. The results indicate that there were no significant changes in pH or titratable acidity following all treatments. Yet, notable differences in juice color were observed. The use of sonication and thermosonication resulted in an increase in β-carotenoid levels. Additionally, total phenolic content and antioxidant activities were observed to increase. All three treatments led to a reduction in ascorbic acid levels relative to the control. However, the complete elimination of microbial growth was observed during the thermal treatment. Compared to other approaches, sonication has been shown to be notably more efficacious in enhancing both the flavor and aroma. Sonication has been observed to improve the perceived bitterness to a certain degree. These findings support the potential of sonication as an alternative preservation method for Adajamir juice, offering enhanced quality and sensory acceptance.